The COVID-19 Pandemic and Global Food Security - Mardones, Fernando O.; Rich, Karl M.; Boden, Lisa A.; Moreno-Switt, Andrea I.; Caipo, Marisa L.; Zimin-Veselkoff, Natalia; Alateeqi, Abdulaziz M.; Baltenweck, Isabelle (Frontiers in Veterinary Science, 2020)
We present scientific perspectives on the impact of the COVID-19 pandemic and global food security. International organizations and current evidence based on other respiratory viruses suggests COVID-19 is not a food safety issue, i.e., there is no evidence associating food or food packaging with the transmission of the virus causing COVID-19 (SARS-CoV-2), yet an abundance of precaution for this exposure route seems appropriate. The pandemic, however, has had a dramatic impact on the food system, with direct and indirect consequences on lives and livelihoods of people, plants, and animals. Given the complexity of the system at risk, it is likely that some of these consequences are still to emerge over time. To date, the direct and indirect consequences of the pandemic have been substantial including restrictions on agricultural workers, planting, current and future harvests; shifts in agricultural livelihoods and food availability; food safety; plant and animal health and animal welfare; human nutrition and health; along with changes in public policies. All aspects are crucial to food security that would require “One Health” approaches as the concept may be able to manage risks in a cost-effective way with cross-sectoral, coordinated investments in human, environmental, and animal health. Like climate change, the effects of the COVID-19 pandemic will be most acutely felt by the poorest and most vulnerable countries and communities. Ultimately, to prepare for future outbreaks or threats to food systems, we must take into account the Sustainable Development Goals of the United Nations and a “Planetary Health” perspective.